Evaluation of self-generating facilities as interruptible loads using hourly load profiles - Espenido, Marti Sandino P.
In the current market set-up of the Philippine Wholesale Electricity Spot Market (WESM), the demand is unable to react to the prices. This results to the exposure of WESM participants, particularly Distribution Utilities and consequently the people they deliver power to, to the risks of price spikes. On the other hand, there is a total of 310MW of capacity distributed among self-generating facilities in Luzon. To harness and quantify the benefit from the untapped capacity of self-generating facilities, the effects of dispatching these facilities across variations of price triggers and reserve triggers were studied. In this thesis, hourly load profiles were assumed for all self-generating facilities and these load profiles were aggregated according to different load categories. These load categories took into consideration the ease of switching between grid sourced power and the generators of the self-generation facilities. Depending on the hourly status of the trigger used, the resulting hourly demand was then subtracted from the demand of the Luzon grid due to the assumption that the self-generating facilities would be dispatched. The reduction in load for affected intervals then resulted to a reduction in price. The reduction in grid demand could also result to fewer instances of generator deficiency. The resulting reduction on the Load Weighted Average Price during each simulation period was the basis for the analysis. In the simulation periods taken into consideration, it was seen that it would be possible to have a drop of 14% in the Load Weighted Average Price during periods of high prices and a price reduction of 1% during normal condition.